PENERIMAAN PERILAKU DISFUNGSIONAL AUDIT: PENDEKATAN KARAKTERISTIK PERSONAL AUDITOR (SURVEY PADA KAP DI KOTA SURABAYA) - Hermanto, Benedicta Angelina Budi; Hariyanto, Simon; Wardani, Rr. Puruwita (Widya Mandala Surabaya Catholic University, 2012)
Dysfunctional audit behavior is a deviant behavior by an auditor which may affect either directly or indirectly the audit quality. One of many ways to improve the audit quality is decreasing the dysfunctional audit behavior. The first step for initiating the efforts to decrease the dysfunctional audit behavior is knowing the factors that caused auditors will accept such behavior. This study aims to examine and obtain empirical evidence about the influence of auditor’s personal characteristics such as performance, locus of control, and turnover intention to the acceptance of dysfunctional audit behavior. Population of this study is auditors who work in public accountant firms in Surabaya. Based on website of Institut Akuntan Publik Indonesia (IAPI), there are 44 public accountant firms in Surabaya in 2013. Data collection techniques used in this study was convinience sampling. Sample of this study was 50 auditors. Data used in this study was primary data in the forms of questionnaire and the results processed using multiple linier regression model. The results showed that the locus of control has a positive effect on the acceptance of dysfunctional audit behavior, while performance and turnover intention do not affect the acceptance of dysfunctional audit behavior